2017
DOI: 10.1016/j.jcrysgro.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Thermoelectric Magnetohydrodynamics in directional solidification under a transverse magnetic field

Abstract: The mechanism of macrosegregation and modification to dendrite size and spacing from a transverse magnetic field has been modelled through direct numerical simulation. The primary driver for this mechanism was identified as a strong Lorentz force formed in the interdendritic region, which leads to a large scale flow circulation. The microstructure evolution is modified by convective transport of solute and the predicted morphological features compare favourably to experimental data in the literature. The numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…Moreover, TEMHD convection alters the morphology of the solid-liquid interface in directional solidification by promoting a cellular-to-dendritic transition [12,13]. Such findings have aroused much research interest in TEMHD phenomena in various solidification processes, from both fundamental and technical perspectives [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, TEMHD convection alters the morphology of the solid-liquid interface in directional solidification by promoting a cellular-to-dendritic transition [12,13]. Such findings have aroused much research interest in TEMHD phenomena in various solidification processes, from both fundamental and technical perspectives [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The detachment phenomenon, which has been observed during our in situ experiments, is most likely due to the significant liquid motion generated by the TEM forces acting on the liquid around the dendrite. 23,24 Baltaretu et al 23 showed that strong TEM flows up to 1.4 mm/s may be generated around a 50-lmradius spherical aluminum particle in a 0.08 T transverse magnetic field under a 30-K/cm temperature gradient. These fluid flows could locally increase the liquid composition in the copper and then yield to the remelting of the secondary arm neck, which is the constricted region at the base where the secondary arm joins the primary dendrite trunk.…”
Section: Dendrite Fragmentationmentioning
confidence: 99%
“…Like buoyancy-driven natural flows [5], TEMHD flows driven by the Lorentz forces can alter heat and mass transfer ahead of the crystal/liquid interface and modify the morphology and segregation patterns of the crystal. The influence of TEMHD flows on crystal growth was observed in directional solidification of metallic alloys, where it aroused much research interest [3,[6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%